2003
DOI: 10.1080/00140130310001593595
|View full text |Cite
|
Sign up to set email alerts
|

Sizing and fit of fall-protection harnesses

Abstract: Full-body fall-protection harnesses have been a critical work-practice control technology for reducing the number of fall-related injuries and fatalities among construction workers; yet, very little is known about the fit of these harnesses to the population that wears them. This study evaluated the fit and sizing efficacy of a harness system. Seventy-two male and 26 female construction workers participated in the study. Their body size-and-shape information was measured while they were suspended (with a harne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…It is worth noting that Hsiao et al (2003) reported that traditional anthropometric data were not satisfactory in addressing the harness fit issue. In addition, the traditional linear anthropometric data did not correspond well to the harness strap components and thus were not informative in harness design practice (Hsiao et al 2007).…”
Section: Limitation Of the Study And Direction For Future Harness Designmentioning
confidence: 98%
See 2 more Smart Citations
“…It is worth noting that Hsiao et al (2003) reported that traditional anthropometric data were not satisfactory in addressing the harness fit issue. In addition, the traditional linear anthropometric data did not correspond well to the harness strap components and thus were not informative in harness design practice (Hsiao et al 2007).…”
Section: Limitation Of the Study And Direction For Future Harness Designmentioning
confidence: 98%
“…The same model of scanner was used in study II to register torso images of 600 participants while standing without a harness. The accuracy of the scanning system was tested to an average error of 2.9 mm, ranging from þ6 mm to -6 mm (Hsiao et al 2003). …”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The chart must be based on dimensions that are readily known or easily measured by the harness user or vendor. Body weight and stature are well known to individual workers and have fine correlations with harness fit and thus have been widely used as indices by harness manufacturers (Hsiao, Bradtmiller, & Whitestone, 2003). Equations 1 through 4 were simplified to become Equations 5 through 8 in presenting an updated, body-size-based sizing system.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The accuracy of the scanning system was tested to an average error of 2.9 mm, varying from +6 to −6 mm (Hsiao et al, 2003).…”
Section: Apparatusmentioning
confidence: 99%